Nutritional practices of male and female endurance cyclists - Burke, L. M. (Sports Medicine, 2001)
The nutritional requirements of the training and competition programmes of elite endurance cyclists are challenging. Notwithstanding the limitations of dietary survey techniques, studies of high-level male road cyclists provide important information about nutrient intake and food practices during training and major stage races. Typically, male cyclists undertaking intensive training programmes report a high energy intake (> or = 250 kJ/kg/day) and carbohydrate (CHO) intakes of 8 to 11 g/kg/day. Intakes of protein and micronutrients are likely to meet Recommended Dietary Intake levels, because of high energy intakes. Data on female cyclists are scarce. Stage racing poses an increased requirement for energy and CHO, with daily energy expenditure often exceeding 25 MJ. This must be achieved in the face of practical constraints on the time available for eating, and the suppression of appetite after exhausting exercise. However, studies show that male cyclists riding for professional teams appear to meet these challenges, with the assistance of their medical/scientific support crews. Current dietary practices during cycle tours appear to favour greater reliance on pre-stage intake and post-stage recovery meals to achieve nutritional goals. Recent reports suggest that current riding tactics interfere with previous practices of consuming substantial amounts of fluid and CHO while cycling. Further study is needed to confirm these practices, and to investigate whether these or other dietary strategies produce optimal cycling performance. Other issues that should receive attention include dietary practices of female cyclists, beliefs and practices regarding bodyweight control among cyclists, and the use of supplements and sports foods.